PENGARUH RELIGIUS DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DI SMA NEGERI BANGUN JAYA KABUPATEN MUSI RAWAS - Amrullah Amrullah (UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: Teacher as the main actor who manage education, should have the ability and personality. There are important factors that influence the religious and emotional intelligence. Teachers who have a religious attitude will become a person who has faith and devotion to become the pious, honest, trustworthy and responsible for the work plus the factor of emotional intelligence, a teacher is able to control, manage emotions and can establish a harmonious society with the school community and surrounding communities. This is why the writer to do this research, to see how much influence the religious and emotional intelligence on the performance of State High School teacher Bangun Jaya. The study consists of two independent variables (independent variables) are religious (X1) and emotional intelligence (X2), while the dependent variable (the dependent variable) is the performance of teachers (Y). In this study can be classified as field research with quantitative approach. The method used in this study are associative to see the impact of the issues examined. Data collection techniques for distributing a questionnaire using a Likert scale, every statement has five alternative answers, ie very suitable (SS), Match (S), sometimes (KD), is not appropriate (TS) and was incompatible (STS) number religious statement 19 items, 17 items of emotional intelligence and performance of teachers 19 items. The population of this research with the subject teacher at National High School Bangun Jaya. Data were analyzed using simple and multiple linear regression. The results of data analysis using SPSS Windows 16.0 shows that: First, there is a low impact on the performance of religious teacher at National High School Bangun Jaya. With the value of R is 0.0354 lies between 0.20 to 0.399. Secondly, there is a considerable influence of emotional intelligence on the performance of schools in the National High School Bangun Jaya. With the value of R is 0.540 lies between 0.40 to 0.599. Third, there is a significant influence of religious and emotional intelligence on the performance of teachers at the National High School Bangun Jaya. With the value of R is 0.461 lies between 0.40 to 0.599.